2007
DOI: 10.1590/s0103-90162007000400013
|View full text |Cite
|
Sign up to set email alerts
|

Phenology and morphological diversity of sweet potato (Ipomoea batatas) landraces of the Vale do Ribeira

Abstract: The phenotypic diversity of sweet potato (Ipomoea batatas) landraces was assessed using morphological traits, verifying how this diversity is distributed among the households and settlements of the Vale do Ribeira, Brazil. A total of 74 accessions, involving 53 landraces, collected from 30 households distributed among 18 settlements that practice traditional agriculture in the municipalities of Iguape, Ilha Comprida, and Cananeia, as well as four commercial varieties acquired in markets of Iguape and Piracicab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
1
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 13 publications
7
37
1
8
Order By: Relevance
“…However Veasey et al (2007) observed a predominance of very superficial lobe (40%) and a much lower frequency of moderate lobe than in the present study, of around 15.0%.…”
Section: Resultscontrasting
confidence: 87%
See 4 more Smart Citations
“…However Veasey et al (2007) observed a predominance of very superficial lobe (40%) and a much lower frequency of moderate lobe than in the present study, of around 15.0%.…”
Section: Resultscontrasting
confidence: 87%
“…Daros et al (2002) reported the pink color as predominant (50%). However, Chávez et al (2006) and Veasey et al (2007) reported predominance of cream coloring while Ritschel & Huamán classified the skin color as white for 41.2% of the accessions, and the second greatest frequency was for the pink coloring, represented by 28.6% of the accessions studied.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations